High-strength complex-phase hot-rolled wire rod for 1960MPa-grade stranded wire and manufacturing method of high-strength complex-phase hot-rolled wire rod
Through high-carbon B-containing chemical composition and online molten salt rapid quenching technology, a hot-rolled wire rod with a complex phase structure is formed, which solves the problems of smelting difficulty caused by high-carbon alloy elements and limited cooling capacity of the air-cooling line, and realizes the production of high-strength and high-plasticity hot-rolled wire rod, which is suitable for the manufacture of 1960MPa grade steel strands.
Patent Information
- Application Number
- CN202511308680.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-15
- Publication Date
- 2025-10-21
- Estimated Expiration
- 2045-09-15
AI Technical Summary
The existing technology for producing hot-rolled wire rods for 1960MPa grade steel strands has the problems of increased smelting difficulty and cost due to the high carbon alloying element content, brittleness and strength reduction caused by the aggregation of network carbides, and the cooling capacity limitation of the air-cooled line leading to structural unevenness and fluctuations in mechanical properties, making it difficult to meet the demand for high-strength strands.
The high-carbon B-containing chemical composition design is combined with online molten salt rapid quenching and roller slow cooling processes. By controlling the formation and tempering of quenched bainite and sorbite structures, a complex phase structure is formed, including tempered sorbite and tempered bainite, which avoids the formation of abnormal structures and improves the strength-plasticity matching.
It simplifies the component system, reduces material costs, improves the strength and plasticity of hot-rolled wire rods, reduces the risk of wire breakage during drawing and torsion, and meets the manufacturing needs of high-strength stranded wire.
Smart Images

Figure CN120818666A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field related to hot-rolled wire rods, and particularly relates to a high-strength multi-phase hot-rolled wire rod for 1960MPa grade stranded wire and a manufacturing method thereof. Background Art
[0002] With the continuous expansion of fields such as machinery, bridges, highways, and new energy, the market demand for steel strands, as important connecting and anchoring mechanisms, continues to rise. For large-scale engineering projects, wire drawing can maximize the performance of wire rods and achieve lightweighting. Increasing the strength of steel wire products can reduce material usage and energy consumption. This has led to higher strength requirements for the hot-rolled wire rod base material used in strands.
[0003] Currently, 1960MPa-grade steel strands are mainly produced using alloy products with a carbon content of 0.87% in combination with a Stelmor air-cooling line. For example, patent CN112301287B discloses prestressed steel strands, wire rods for prestressed steel strands, and methods for producing the same. These use C-Si-Mn-Cr-V-Al, combined with a Stelmor air-cooling line for rapid followed by slow cooling, to produce wire rods with a diameter of 16mm and a structure dominated by sorbite and containing a small amount of pearlite. The wire rods achieve a tensile strength of 1320-1380MPa and a cross-sectional reduction of 28% or more. However, the following are its drawbacks: On the one hand, the increase in the content of carbon and multiple alloy elements will increase the difficulty of smelting and the cost of alloys. Limited by the maximum cooling capacity of the air-cooled wire, at high carbon content, alloy elements such as Cr and V will further reduce the solubility of carbon in austenite, causing carbon to diffuse to the grain boundaries, making it difficult to disperse evenly during the cooling process. It will gather along the austenite grain boundaries to form more continuous and coarse network carbides. The network carbides cut the matrix along the grain boundaries, causing the plastic and toughness properties of the wire rod to drop significantly. During subsequent stranded wire drawing, it is easy to break along the grain at the stress concentration point, and it will break brittlely during torsion because it cannot withstand shear deformation. However, in order to reduce material costs and the difficulty of controlling network carbides, it is chosen to reduce carbon and omit alloying elements. Relying solely on pearlite strengthening will result in a large loss of strength, making it difficult to meet the performance requirements of high-strength stranded wire.
[0004] On the other hand, Cr, Mn and other elements are elements that improve the hardenability of wire rod. As the diameter of wire rod decreases, the local enrichment of carbon and alloy elements produced during continuous casting or rolling will be more concentrated. Affected by the unstable temperature control of the air-cooling line, especially in order to minimize the influence of network carbides and promote the refinement of tissue lamellar layers, strong air cooling is required after spinning, which will further aggravate the temperature difference between the surface and core of wire rod or the local temperature difference, and easily form uncontrollable martensite or bainite structure on the surface or locally. Limited by the minimum cooling capacity of the air-cooling line, abnormal structure will bring greater brittleness to the wire rod, and affected by the uneven lamellar structure, it will be further The step-by-step increase in radial differences in strength and plasticity and fluctuations in mechanical properties brings great risks to the production of hot-rolled wire rods. Abnormal tissues will also become stress concentration points during subsequent drawing or torsion in stranded wire manufacturing, causing microcracks and rapid expansion, affecting the yield rate and production efficiency of stranded wire steel. In order to reduce the risk of low-temperature brittle tissues such as martensite, the choice of reducing air-cooling intensity will increase the level of network carbides, resulting in a surge in material brittleness. The continuous cooling of the air-cooling line and the coarsening of the tissue layers will lead to a loss of strength and toughness. The network carbides and coarse pearlite will also become stress concentration sources during drawing, and cannot meet the plasticity requirements of torsion processing. Summary of the Invention
[0005] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a high-strength multi-phase hot-rolled wire rod for 1960MPa grade stranded wire and a manufacturing method thereof, which can simplify the component system, reduce material costs, realize multi-phase structure regulation, take into account the strength and plasticity matching of the wire rod and rapid production, and help reduce the risk of wire breakage during the drawing and torsion process of the stranded wire steel.
[0006] The technical solution adopted by the present invention to solve its technical problem is: A method for manufacturing high-strength multi-phase hot-rolled wire rod for 1960 MPa grade stranded wire, the manufacturing method comprising: The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.79% to 0.83%, Si: 0.20% to 0.40%, Mn: 0.67% to 0.78%, B: 0.001% to 0.008%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; the wire rod is spun into wire rod at a spinning temperature of ≥890°C, and then subjected to online molten salt In the rapid quenching treatment, the wire rod first undergoes the front-end molten salt treatment, so that the wire rod is cooled at a cooling rate of ≥36℃ / s, and enters the mixed phase region of bainite and pearlite from the austenite state, forming a structure mainly composed of quenched bainite and sorbite. The wire rod then undergoes the rear-end molten salt treatment to increase the molten salt temperature, promote the isothermal tempering of the quenched bainite and sorbite structures, and finally passes through the roller to slowly cool, and is made into a hot-rolled wire rod with a microstructure consisting of tempered sorbite, tempered bainite and ferrite.
[0007] The chemical composition and mass percentage of the hot rolled wire rod are designed based on the following: (1) Carbon: C is a solid solution strengthening element in steel and has a relatively low price. Carbon dissolves in the iron matrix, forms cementite with iron, and forms carbides in quenched bainite or bainite, which can provide solid solution strengthening effect, hinder dislocation slip, and improve the strength of steel. Appropriate carbon concentration can increase the driving force of bainite transformation, promote the refinement of pearlite lamellae to form bainite structure during rapid quenching and cooling, and improve the matrix strength. However, if the C content is too high, it will make it more difficult to control the center segregation, network carbides and coarse carbides of high carbon steel billets. The enrichment of carbon in austenite will increase the risk of martensite precipitation, affecting toughness and processing plasticity. Therefore, in order to take into account the high strength requirements of 1960MPa grade stranded wire, reduce the difficulty of controlling the uniformity of the structure and abnormal structure, and adapt to the control of complex phase structure, the carbon content is appropriately reduced, and the mass percentage of C is controlled to be 0.79%~0.83%.
[0008] (2) Silicon: The Si element can significantly improve the hardness and strength of the matrix by dissolving in the iron matrix through solid solution strengthening. In the phase transformation process from austenite to quenched bainite and troostite mixed structure, silicon can hinder the diffusion of carbon atoms into cementite and inhibit the growth of cementite, which helps to promote bainite transformation, maintain the refinement of troostite lamellae and the uniformity of bainite structure, and avoid the strength loss or toughness deterioration caused by carbide coarsening. However, excessive silicon will promote decarburization, increase the difficulty of softening, and lead to a decrease in the plasticity of steel. In the subsequent processing links such as wire drawing and torsion, the steel will break due to increased brittleness, affecting the yield rate of the stranded wire. Therefore, in order to adapt to the regulation of phase transformation structure by online molten salt rapid quenching treatment, the mass percentage of Si is controlled to be 0.20%~0.40%.
[0009] (3) Manganese: Mn is an austenite stabilizing element that can expand the stable range of austenite and significantly improve the hardenability of steel. It affects the phase transformation dynamics by reducing the critical cooling rate of austenite, causing the pearlite transformation temperature to shift to a low temperature and be closer to the transformation temperature range of bainite. In the rapid quenching stage of the molten salt in the front section, it avoids the coarsening of pearlite or excessive precipitation of ferrite, thereby promoting the rapid formation of a mixed structure of quenched bainite and troostite at the same time. At the same time, in the isothermal tempering stage of the molten salt in the back section, it can stabilize the quenched bainite and troostite structures, inhibit the coarsening of carbides, and avoid the coarsening of the structure. The strength is reduced or the toughness is deteriorated, but when the Mn content is too high, it will increase the element segregation during the solidification process of the steel billet. The austenite in the Mn-rich area is more stable, and low-temperature martensite structure is easily formed during the cooling process, which increases the risk of abnormal tissue precipitation and local brittleness, becoming a stress concentration point during subsequent wire drawing and torsion, causing microcracks. At the same time, it increases the difficulty of tempering softening, thereby reducing the plasticity of the wire rod and being unfavorable for rapid production. Therefore, in order to take into account the control of the complex phase structure of the hot-rolled wire rod and reduce the difficulty of abnormal structure and tempering control, the mass percentage of Mn is controlled at 0.67%~0.78%.
[0010] (4) Boron: Trace amounts of boron are preferentially enriched at the austenite grain boundaries in steel, which can effectively improve the hardenability of steel and cause ferrite to precipitate at the austenite grain boundaries, so that a sufficient proportion of quenched bainite can be formed under rapid quenching cooling, reducing the difference between the surface and core structures. At the same time, it can inhibit the migration and coarsening of carbides to the grain boundaries during tempering, providing a stable grain boundary basis for the subsequent complex phase structure after tempering. However, the price of boron is relatively high, and excessive addition is not conducive to controlling material costs. At the same time, excessive boron will cause brittle phase precipitation, destroying the plasticity and processing properties of the material. Therefore, the mass percentage of boron is controlled to be 0.001%~0.008%.
[0011] (5) Phosphorus and sulfur: P and S are impurity elements. The lower the better. Therefore, P is controlled to be ≤ 0.015% and S is controlled to be ≤ 0.015%.
[0012] The above-mentioned wire rod is designed with a high-carbon B-containing chemical composition, which does not rely on high Cr, V and other alloying elements, can simplify the composition system, appropriately reduce material costs, smelting difficulty and the segregation problem caused by high alloying elements, and at the same time, cooperate with Mn and trace B elements to regulate the hardenability of the wire rod. By changing the stability and phase transformation dynamics of austenite, the pearlite and bainite transformation ranges are overlapped and close, which provides favorable conditions for the synchronous mixed phase transformation of quenched bainite and troostite, the inhibition of lamellar coarsening and excessive precipitation of ferrite, and the convenience of rapid tempering of the organization. On this basis, the wire rod adopts a higher spinning temperature to keep the organization in a high-temperature austenite state, inhibit the segregation of components, avoid the formation of network carbides at too low a temperature, and provide favorable conditions for promoting bainite quenching and lamellar refinement. After spinning, the wire rod is directly subjected to online molten salt rapid quenching treatment without air cooling: 1. Compared with the air-cooled wire, which is limited by the maximum cooling capacity and unstable cooling control, and cannot effectively control the network carbides and abnormal tissues, on the one hand, the thermal conductivity of molten salt is higher than that of air-cooled wire, and the efficient heat conduction can promote the rapid cooling of the wire rod, and quickly skip the high-temperature range where carbides are easily precipitated from the high-temperature austenite state, avoid staying in the high-temperature range for a long time, reduce the segregation and precipitation of carbon at the austenite grain boundary, effectively inhibit the network carbides, and reduce the brittleness of the tissue. On the other hand, the high cooling rate of the wire rod can make the surface and core of the wire rod enter the lower temperature bainite and pearlite mixed phase region from the high-temperature austenite state, avoid the nose temperature of the pearlite transformation, form a large degree of supercooling, and trigger a small amount of The quenched bainite transforms rapidly and refines the pearlite to form a sorbite structure with finer interlamellar spacing, avoiding the formation of coarsened pearlite or proeutectoid ferrite due to insufficient cooling rate, which can enhance the strengthening effect of carbon and make up for the strength loss caused by reducing carbon and eliminating alloying elements. At the same time, when the wire rod passes through the molten salt, the molten salt can cover the surface of the wire rod, which can reduce the temperature gradient between the wire rod surface and the core compared to air or combined with water mist cooling and air cooling control. At the same time, it can avoid the influence of local overcooling and segregation to form a brittle martensite structure, making the conventionally regarded abnormal quenched bainite structure more controllable, effectively controlling the abnormal structure, improving the uniformity of the structure, reducing the fluctuation of mechanical properties, and providing a basis for the consistency of subsequent stranding processing.
[0013] Second, compared with the limited minimum cooling capacity and continuous cooling limit of the air cooling line, which cannot improve the brittleness of the structure, on the one hand, with the rapid quenching of the front molten salt treatment, it can promote the full phase transformation of the structure and avoid the stress concentration of coarse network carbides and coarse pearlite. The molten salt temperature of the latter molten salt treatment is higher than that of the former molten salt treatment, which can avoid the residual austenite and the continued formation of martensite brittle structure in the subsequent cooling process; on the other hand, the molten salt can control the wire rod to be consistent with the molten salt temperature, and perform isothermal treatment instead of continuous cooling. As the molten salt treatment time at a higher molten salt temperature is prolonged, The enhanced atomic diffusion capacity can release the transformation stress through dislocation movement, grain boundary sliding, etc., so that the dislocation density of the quenched bainite is reduced, and it is transformed into tempered bainite with retained strength but better toughness, significantly reducing the brittleness of the structure. At the same time, the stress of the bainite structure is released, and it is transformed into tempered bainite with better plasticity. Finally, it is subjected to roller slow cooling treatment. The slow cooling promotes further toughening of the wire rod structure and improves the tempering softening effect of the wire rod. Then, the brittleness of the structure is effectively improved through tempering state regulation to regulate the strength-plasticity matching of the wire rod, significantly reducing the risk of brittle fracture caused by stress concentration.
[0014] Before the rolling, appropriate soaking temperature and time in the heating furnace are selected to austenitize the steel billet, improve composition uniformity and heating consistency, reduce composition segregation, and avoid grain coarsening caused by excessively high temperature and excessively long time in the furnace. In the preferred technical solution, before the rolling, the soaking temperature of the heating furnace is controlled to be 1180~1220℃, and the time in the furnace is 150~220min.
[0015] During the rolling, selecting a higher initial rolling temperature can improve the rolling plasticity of the steel billet, reduce deformation resistance and wear on the rolling line, and increase the rolling speed. Selecting a suitable final rolling temperature and final rolling reduction can generate a large number of dislocations that provide nucleation points for recrystallization, promote dynamic recrystallization during the final rolling process, refine the grains, and reduce internal defects. In the preferred technical solution, during the rolling, the initial rolling temperature is controlled to be 1080~1100℃, the final rolling temperature is 900~940℃, and the final rolling reduction is 25%~30%.
[0016] During the spinning process, the spinning temperature can be further controlled to provide a suitable starting temperature for online molten salt rapid quenching and avoid the risk of grain coarsening caused by excessively high spinning temperature. In a preferred technical solution, during the spinning process, the spinning temperature is controlled to be 890-930°C.
[0017] The molten salt temperature of the front-stage molten salt treatment is in the mixed phase region of bainite and pearlite. The lower the molten salt temperature and the longer the treatment time, the more it cooperates with the hardenability of B, which is beneficial to inhibiting the network carbides and lamellar coarsening, increasing the supercooling of austenite, and the shear driving force of the needle-shaped quenched bainite transformation is dominant, and the nucleation rate is accelerated, which is beneficial to promoting the refinement of the sorbite structure lamellar, and can improve the matrix strength. However, if the molten salt temperature is too low and the treatment time is too long, the quenched bainite transformation increases and the internal stress of the structure increases, which will increase the difficulty of subsequent tempering softening, affect the plasticity and production efficiency of the wire rod, and increase production energy consumption. It may even form abnormal martensite structure due to supercooling, resulting in increased tissue brittleness. On the contrary, if the molten salt temperature is higher and the treatment time is too long, the quenched bainite transformation increases and the internal stress of the structure increases. The shorter the time, the stronger the diffusion driving force of the sorbite transformation, the easier it is to form a sorbite lamellar structure and reduce the difficulty of improving the plasticity of tempering. However, if the molten salt temperature is too high and the treatment time is too short, it is not conducive to the formation of quenched bainite. The sorbite lamellar layer has the risk of coarsening, thereby losing the matrix strength. Therefore, the molten salt temperature and treatment time of the front molten salt treatment can be controlled to control the wire rod to quickly enter the bainite and pearlite mixed phase region from the high-temperature austenite state, forming a structure dominated by a small amount of quenched bainite and a large part of the sorbite complex phase with fine lamellar spacing, so as to make organizational preparations for the rear molten salt treatment. In the preferred technical solution, the molten salt temperature of the front molten salt treatment is 400~450℃, and the treatment time is 30~200s.
[0018] The front-stage molten salt treatment uses a larger molten salt circulation volume, which can promote the rapid cooling and heat transfer of the wire rod, while controlling the temperature rise of the molten salt and improving the uniformity of continuous treatment. In the preferred technical solution, the molten salt circulation volume of the front-stage molten salt treatment is 460~660t / h, and the molten salt temperature rise is ≤10℃.
[0019] The molten salt temperature of the latter molten salt treatment is appropriately higher than that of the former molten salt. The higher the molten salt temperature and the longer the treatment time, the higher the diffusion rate of carbon atoms can be, which provides more driving force for the isothermal tempering and toughening of quenched bainite and troostite structures, reduces the stress and dislocation density in the quenched bainite, improves the plasticity and toughness of the structure, and the uniformity of the tempering of the surface and core structures. However, if the molten salt temperature is too high and the treatment time is too long, the atomic diffusion rate will be accelerated, and the cementite of the quenched bainite and troostite will gradually coarsen and aggregate, which will cause excessive softening and significantly lose the matrix strength, while also bringing about an increase in production cycle and energy consumption. On the contrary, the lower the molten salt temperature and the shorter the treatment time, the slower the diffusion rate of carbon atoms, which is conducive to reducing The risk of carbide coarsening and excessive strength loss, reduced production energy consumption, and improved production efficiency, but the molten salt temperature is too low and the treatment time is too short, which makes it difficult to provide more thermal power for tempering, affecting stress release and tempering effects, increasing the brittleness of the wire rod, and the difference between the surface and core structures. When subjected to stress, the core is prone to fracture due to stress concentration. Therefore, the molten salt temperature and treatment time of the latter molten salt can be further controlled to promote isothermal tempering of the formed quenched bainite and troostite structures, taking into account rapid treatment and avoiding excessive softening, so as to regulate the strength-plasticity matching of the wire rod. In the preferred technical solution, the molten salt temperature of the latter molten salt treatment is 450~480℃, and the treatment time is 50~200s.
[0020] Since the temperature difference of molten salt between the front-stage molten salt treatment and the rear-stage molten salt treatment is small, the molten salt circulation volume of the rear-stage molten salt treatment is smaller than that of the front-stage molten salt treatment, which can appropriately reduce production energy consumption, while accurately controlling the molten salt temperature rise and improving the consistency of wire rod processing in continuous production. In the preferred technical solution, the molten salt circulation volume of the rear-stage molten salt treatment is 320~410t / h, and the molten salt temperature rise is ≤3°C.
[0021] Since the wire rod has undergone sufficient phase transformation after the online molten salt rapid quenching treatment, the formation of low-temperature abnormal structure during the roller slow cooling can be avoided. Moreover, since the temperature of the wire rod is relatively high after leaving the molten salt, the selection of an appropriate slow cooling rate can avoid insufficient plasticity of the wire rod due to insufficient slow cooling. At the same time, slow cooling promotes further toughening of the wire rod structure and improves the tempering and softening effect of the wire rod. In the preferred technical solution, the roller slow cooling controls the wire rod to be cooled to below 280°C at a slow cooling rate of ≤0.6°C / s for coiling.
[0022] In the preferred technical solution, the roller slow cooling adopts the method of controlling the opening of the insulation cover, blowing hot air ≥250°C to the conveying roller during the online molten salt rapid quenching treatment, and the conveying roller conveys the wire rod through the insulation cover to control the slow cooling of the wire rod, which can further recycle the heat energy of the online molten salt rapid quenching, reduce production energy consumption, and promote the rapid offline of the wire rod.
[0023] A high-strength multi-phase hot-rolled wire rod for 1960 MPa grade stranded wire is manufactured by any of the above-mentioned methods for manufacturing the high-strength multi-phase hot-rolled wire rod for 1960 MPa grade stranded wire.
[0024] The above-mentioned wire rod is designed with a high carbon component containing trace amounts of B. Compared with the high-alloy high-carbon steel wire rod used for air-cooled wire used for steel strands, it can simplify the composition system and reduce material costs. At the same time, it can effectively avoid the risk of network carbides caused by high carbon content. It uses molten salt for rapid quenching to simultaneously transform the quenched bainite and the sorbite structure with finer interlamellar spacing, reducing the proportion of ferrite. The fine needle-like structure and high dislocation density of the quenched bainite make its strength higher than that of the sorbite. After isothermal tempering and transformation into tempered bainite, the needle-like morphology of the tempered bainite is retained but the substructure is more stable, which can reduce grain boundary embrittlement, retain strength and significantly improve brittle characteristics. The sorbite structure is finer than the pearlite lamellar layer and has better strength and toughness. After isothermal tempering, the stress is released and it is transformed into The intermediate transition state of the spheroidized microstructure is tempered bainite, and the microstructure stress is further released, which can further improve the microstructure plasticity. Then, through the regulation of the complex phase structure and the tempering state of the structure, the strengthening effect of the carbon element is maximized, which makes up for the strength loss caused by reducing the carbon content and eliminating the alloying elements, and makes the quenched bainite phase transformation, which is conventionally regarded as an abnormal structure, more controllable and utilized, and avoids the adverse effects of martensite on the plasticity and toughness of the structure, and avoids the adverse effects of coarse pearlite on the matrix strength and microstructure uniformity, reduces the performance difference between the surface and the core, and effectively improves the overall strength and plasticity of the wire rod based on the composition design, reduces the stress concentration and brittle fracture risk in the subsequent wire drawing and torsion process, and meets the manufacturing needs of high-strength stranded wire.
[0025] In the multiphase structure, the higher the volume percentage of tempered bainite, the higher the plasticity and toughness; the finer the interlamellar spacing of the tempered bainite and the higher the volume percentage of the tempered bainite, the stronger the resistance to dislocation movement and the higher the strength. In the preferred technical solution, the volume percentage of the tempered bainite is 68%~78%, the interlamellar spacing is 70~115nm, and the volume percentage of the tempered bainite is 20%~30%.
[0026] In the preferred technical solution, the network carbide level of the hot-rolled wire rod is level 0, and the mechanical property difference is ≤38MPa. It can effectively control the adverse effects of the network carbide on the plastic toughness, organizational uniformity and fatigue performance of the matrix, while suppressing abnormal organizations such as martensite and coarse pearlite. The organizational uniformity from the surface to the core of the wire rod is higher, which can effectively reduce the fluctuation of mechanical properties, thereby improving processing stability and reducing stress concentration and brittle fracture during subsequent wire drawing or torsion twisting.
[0027] In the preferred technical solution, the diameter of the hot-rolled wire rod is 8.0~15.0mm, the tensile strength is 1330~1380MPa, and the cross-sectional shrinkage rate is 35%~40%. The hot-rolled wire rod has a smaller specification and higher tensile strength, which can reduce the subsequent drawing passes and quickly reach the target diameter and strength of the stranded wire. At the same time, it has a higher cross-sectional shrinkage rate, which can meet the deformation requirements during stranded wire drawing and torsion twisting, and improve the stability and yield rate of large deformation processing.
[0028] Compared with the prior art, the present invention has the following beneficial effects: (1) Aiming at the current situation that 1960MPa grade steel strand wire rod is mainly produced by combining alloy products with 0.87% carbon content with air cooling line, it is very easy to produce brittle structures such as network carbide and martensite, which leads to the fracture of hot rolled wire rod during drawing and torsion. The present invention adopts the design of carbon-containing B chemical composition combined with online molten salt rapid quenching technology, which can control the wire rod from the high-temperature austenite state to enter the mixed phase region of bainite and pearlite, forming a structure mainly composed of quenched bainite and fine lamellar spacing sorbite structure. Then, the temperature is appropriately raised to promote the isothermal tempering of the formed quenched bainite and sorbite structure to regulate the strength-plasticity matching of the wire rod, which can effectively suppress abnormal structures such as network carbide, martensite, coarse pearlite, etc. Finally, the roller slow cooling promotes the further toughening of the wire rod structure, taking into account rapid production, and can achieve complex phase structure control and high strength-plasticity matching of the wire rod, with good industrial adaptability.
[0029] (2) Aiming at the defects of 1960MPa grade steel strand wire rod material such as high cost, insufficient strength and plasticity or large fluctuation of mechanical properties, the present invention adopts a high carbon carbon component design containing trace amount of B, which can simplify the component system and reduce material cost. The microstructure includes a complex phase structure composed of tempered bainite, tempered bainite and ferrite. By regulating the complex phase structure and the tempering state of the structure, the strengthening effect of the carbon element is maximized, and the strength loss caused by reducing the carbon content and eliminating the alloy elements is compensated. The adverse effects of martensite on the plasticity and toughness of the structure are avoided, and the adverse effects of coarse pearlite on the matrix strength and uniformity of the structure are avoided, and the fluctuation of mechanical properties is effectively reduced. On the basis of the component design, the overall strength and plasticity of the wire rod are effectively improved, and the tensile strength can reach 1330~1380MPa and the cross-sectional shrinkage rate can reach 35%~40%. It can be used in the fields of 1960MPa grade steel strand, which is beneficial to reduce the stress concentration and brittle fracture risk in the subsequent drawing and torsion process, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The above and / or additional aspects and advantages of the present invention will become apparent and readily understood from the following description of the embodiments with reference to the accompanying drawings, in which: Figure 1 is a metallographic structure diagram of Example 1 of the present invention; Figure 2 is a metallographic structure diagram of Example 2 of the present invention; Figure 3 This is the metallographic structure diagram of Example 3 of the present invention. DETAILED DESCRIPTION
[0031] The embodiments described below with reference to the accompanying drawings are exemplary and are only for illustration and do not limit the description of the features and characteristics of the present invention. They are to propose the best way to implement the present invention, are intended to be used to explain the present invention, and are sufficient to enable those skilled in the art to practice the invention, but should not be understood as limiting the scope of the present invention, which is limited only by the appended claims; the hot-rolled wire rods obtained in the following embodiments and comparative examples are subjected to microstructure and performance testing, including: tensile testing using "GB-T228.1-2021 Metallic Materials Tensile Testing Part 1: Room Temperature Test Method" to obtain tensile strength and cross-sectional reduction rate; microstructure testing is performed in accordance with the metal microstructure testing method of GB / T13298 standard; mechanical property same-circle difference test method: take 2 circles of wire rod 5m away from the end of the coil, and divide each circle of wire rod into 8 equal sections with the overlap area as the base point, and take 1 tensile specimen on each section. The extreme difference in strength of the tensile specimens after tensile testing is the mechanical property same-circle difference. Example 1:
[0032] A preferred embodiment of the method for manufacturing high-strength multiphase hot-rolled wire rod for 1960 MPa grade stranded wire according to the present invention, wherein the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.79%, Si: 0.39%, Mn: 0.69%, B: 0.001%, P: 0.013%, S: 0.015%, and the remainder is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt rapid quenching → roller slow cooling → coiling, specifically: The rolling process is used to heat the steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet that can be rolled into plasticity, reduce component segregation and avoid grain coarsening, and roll the steel billet into a wire with a diameter of 11mm through a rolling line after the steel billet leaves the heating furnace. The appropriate rolling temperature and reduction amount are selected to improve the rolling efficiency, and the dynamic recrystallization and grain refinement of the final rolling process are controlled. Specifically: the heating furnace soaking temperature is controlled to be 1195℃, and the furnace time is controlled to be 1195℃. The rolling time is 200min, the initial rolling temperature is 1085℃, the final rolling temperature is 920℃, and the final rolling reduction is 28.5%. The spinning process is used to turn the wire rod out of the rolling line into a wire rod through a spinning mechanism. The wire rod is spread on the roller and transported along the roller. The appropriate spinning temperature is selected to make the wire rod in a high-temperature austenitized state, avoid the precipitation of network carbides in the spinning stage, and provide favorable conditions for the subsequent rapid nucleation of bainite and troostite. Specifically, the spinning temperature is controlled to be 905℃.
[0033] The online molten salt rapid quenching process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first salt bath tank for the front molten salt treatment, so that the wire rod is cooled at a cooling rate of 39°C / s, and quickly skips the network carbide interval from the high-temperature austenite state to the bainite and pearlite mixed phase area, inhibiting the formation of network carbides. The high-temperature austenite phase transforms into a structure mainly composed of a small amount of quenched bainite and a large amount of fine lamellar interlayer sorbite. It is then conveyed by a roller through the second salt bath tank for the rear molten salt treatment. The process of the molten salt treatment in the front stage is to increase the molten salt temperature, reduce the molten salt circulation volume, promote the isothermal tempering of the formed quenched bainite and troostite structures, take into account rapid processing and avoid excessive softening, so as to regulate the strength-plasticity matching of the wire rod. Specifically: the molten salt temperature of the front stage molten salt treatment is 432°C, the processing time is 140s, the molten salt circulation volume is 515t / h, and the molten salt temperature rise is ≤10°C; the molten salt temperature of the rear stage molten salt treatment is 472°C, the processing time is 170s, the molten salt circulation volume is 345t / h, and the molten salt temperature rise is ≤3°C.
[0034] The roller slow cooling process controls the opening of the insulation cover to blow hot air ≥250°C above the two salt baths of the online molten salt rapid quenching treatment to the conveyor roller, and the conveyor roller conveys the wire rod through the insulation cover to promote further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to cool to 274°C at a slow cooling rate of 0.5°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure is as follows Figure 1 shown.
[0035] Comparative Example 1: A method for manufacturing a hot-rolled wire rod, which differs from Example 1 in that: the method is manufactured according to a process flow of rolling → spinning → Stelmor air cooling, specifically: controlling the heating furnace soaking temperature to 1150°C, the furnace time to 215min, the initial rolling temperature to 1060°C, the final rolling temperature to 880°C, and the spinning temperature to 860°C; the Stelmor strong air cooling adopts an air volume of 260,000 m3 per fan. 3 / h, open 1~5# fans at 70%, cool the wire rod at a cooling rate of 6.9℃ / s to 683℃, then open 6~14# fans at 30%, cool the wire rod at a cooling rate of 2.6℃ / s to 270℃, and obtain the hot rolled wire rod after it comes off the line.
[0036] Comparative Example 2: A method for manufacturing a hot-rolled wire rod, which differs from Example 1 in that: the soaking temperature of the heating furnace is controlled to be 1150°C, the furnace time is 215 minutes, the initial rolling temperature is 1055°C, the final rolling temperature is 860°C, and the spinning temperature is 840°C. During the molten salt treatment in the front section of the online molten salt rapid quenching process, the wire rod is cooled at a cooling rate of 32°C / s, and the hot-rolled wire rod product is obtained after it comes off the line. Example 2:
[0037] A preferred embodiment of the method for manufacturing high-strength multiphase hot-rolled wire rod for 1960 MPa grade stranded wire according to the present invention, wherein the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.79%, Si: 0.25%, Mn: 0.72%, B: 0.008%, P: 0.014%, S: 0.015%, and the remainder is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt rapid quenching → roller slow cooling → coiling, specifically: The rolling process is used to heat a steel billet with a specification of 180mm×180mm through a heating furnace to achieve a high-temperature steel billet with rollable plasticity, reduce component segregation and avoid grain coarsening, and roll the steel billet into a wire rod with a diameter of 8mm through a rolling line after the steel billet leaves the heating furnace. Appropriate rolling temperature and reduction are selected to improve rolling efficiency, and dynamic recrystallization and grain refinement are controlled during the final rolling process. Specifically, the heating furnace soaking temperature is controlled to be 1180°C, the furnace time is 220min, the initial rolling temperature is 1080°C, the final rolling temperature is 900°C, and the final rolling reduction is 30%; the wire-spinning process is used to convert the wire rod leaving the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on a roller and transported along the roller. A suitable wire-spinning temperature is selected to keep the wire rod in a high-temperature austenitized state, avoid the precipitation of network carbides in the wire-spinning stage, and provide favorable conditions for the subsequent rapid nucleation of bainite and sorbite. Specifically, the wire-spinning temperature is controlled to be 890°C.
[0038] The online molten salt rapid quenching process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first salt bath tank for the front stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 36°C / s, and quickly skips the network carbide interval from the high-temperature austenite state to the bainite and pearlite mixed phase area, inhibiting the formation of network carbides. The high-temperature austenite phase transforms into a structure mainly composed of a small amount of quenched bainite and a large amount of fine lamellar interlayer sorbite. It is then conveyed by a roller through the second salt bath tank for the rear stage molten salt treatment. The process of the molten salt treatment in the front stage is to increase the molten salt temperature, reduce the molten salt circulation volume, promote the isothermal tempering of the formed quenched bainite and troostite structures, take into account rapid processing and avoid excessive softening, so as to regulate the strength-plasticity matching of the wire rod. Specifically, the molten salt temperature of the front stage molten salt treatment is 450°C, the processing time is 200s, the molten salt circulation volume is 460t / h, and the molten salt temperature rise is ≤10°C; the molten salt temperature of the rear stage molten salt treatment is 480°C, the processing time is 50s, the molten salt circulation volume is 320t / h, and the molten salt temperature rise is ≤3°C.
[0039] The roller slow cooling process controls the opening of the insulation cover to blow hot air ≥250°C above the two salt baths of the online molten salt rapid quenching treatment to the conveyor roller, and the conveyor roller conveys the wire rod through the insulation cover to promote further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to cool to 271°C at a slow cooling rate of 0.6°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure is shown as follows. Figure 2 shown.
[0040] Comparative Example 3: A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that: during the front-end molten salt treatment of the online molten salt rapid quenching process, the wire rod is cooled at a cooling rate of 40°C / s, the molten salt temperature of the front-end molten salt treatment is 395°C, the treatment time is 210s, and the hot-rolled wire rod finished product is obtained after coming off the line.
[0041] Comparative Example 4: A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that: during the front-end molten salt treatment of the online molten salt rapid quenching process, the wire rod is cooled at a cooling rate of 33°C / s, the molten salt temperature of the front-end molten salt treatment is 475°C, the treatment time is 25s, and the hot-rolled wire rod finished product is obtained after coming off the line. Example 3:
[0042] A preferred embodiment of the method for manufacturing high-strength multiphase hot-rolled wire rod for 1960 MPa grade stranded wire according to the present invention, wherein the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.81%, Si: 0.4%, Mn: 0.67%, B: 0.005%, P: 0.013%, S: 0.014%, and the remainder is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt rapid quenching → roller slow cooling → coiling, specifically: The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet with rollable plasticity, reduce component segregation and avoid grain coarsening, and roll the steel billet into a wire rod with a diameter of 13mm through a rolling line after the steel billet leaves the heating furnace. Appropriate rolling temperature and reduction are selected to improve rolling efficiency, and dynamic recrystallization and grain refinement are controlled during the final rolling process. Specifically, the heating furnace soaking temperature is controlled to be 1210°C, the furnace time is 175min, the initial rolling temperature is 1095°C, the final rolling temperature is 930°C, and the final rolling reduction is 26%; the wire-spinning process is used to convert the wire rod leaving the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on a roller and transported along the roller. A suitable wire-spinning temperature is selected to keep the wire rod in a high-temperature austenitized state, avoid the precipitation of network carbides in the wire-spinning stage, and provide favorable conditions for the subsequent rapid nucleation of bainite and sorbite. Specifically, the wire-spinning temperature is controlled to be 915°C.
[0043] The online molten salt rapid quenching process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first salt bath tank for the front stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 40°C / s, and quickly passes through the network carbide interval from the high-temperature austenite state to the bainite and pearlite mixed phase area, inhibiting the formation of network carbides. The high-temperature austenite phase transforms into a structure mainly composed of a small amount of quenched bainite and a large amount of fine lamellar interlayer sorbite. It is then conveyed by a roller through the second salt bath tank for the rear stage molten salt treatment. The process of the molten salt treatment in the front stage is to increase the molten salt temperature, reduce the molten salt circulation volume, promote the isothermal tempering of the formed quenched bainite and troostite structures, take into account rapid processing and avoid excessive softening, so as to regulate the strength and plasticity matching of the wire rod. Specifically, the molten salt temperature of the front stage molten salt treatment is 415°C, the processing time is 95s, the molten salt circulation volume is 570t / h, and the molten salt temperature rise is ≤10°C; the molten salt temperature of the rear stage molten salt treatment is 465°C, the processing time is 105s, the molten salt circulation volume is 370t / h, and the molten salt temperature rise is ≤3°C.
[0044] The roller slow cooling process controls the opening of the insulation cover to blow hot air ≥250°C above the two salt baths of the online molten salt rapid quenching treatment to the conveyor roller, and the conveyor roller conveys the wire rod through the insulation cover to promote further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to cool to 276°C at a slow cooling rate of 0.45°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage. Its metallographic structure is as follows Figure 3 shown.
[0045] Comparative Example 5: A method for manufacturing a hot-rolled wire rod, which differs from Example 3 in that the molten salt temperature of the latter molten salt treatment is 490° C., the treatment time is 210 s, and the hot-rolled wire rod product is obtained after the production line is closed.
[0046] Comparative Example 6: A method for manufacturing a hot-rolled wire rod, which differs from Example 3 in that the molten salt temperature of the latter molten salt treatment is 440°C, the treatment time is 45s, and the hot-rolled wire rod product is obtained after the production line is closed. Example 4:
[0047] A preferred embodiment of the method for manufacturing a high-strength multiphase hot-rolled wire rod for 1960 MPa grade stranded wire according to the present invention, wherein the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.83%, Si: 0.35%, Mn: 0.78%, B: 0.004%, P: 0.015%, S: 0.014%, and the remainder is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt rapid quenching → roller slow cooling → coiling, specifically: The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet with rollable plasticity, reduce component segregation and avoid grain coarsening, and roll the steel billet into a wire with a diameter of 15mm through a rolling line after the steel billet leaves the heating furnace. Appropriate rolling temperature and reduction are selected to improve rolling efficiency, and dynamic recrystallization and grain refinement are controlled during the final rolling process. Specifically, the heating furnace soaking temperature is controlled to be 1220°C, the furnace time is 150min, the initial rolling temperature is 1100°C, the final rolling temperature is 940°C, and the final rolling reduction is 25%; the wire-spinning process is used to convert the wire rod leaving the rolling line into a wire rod through a wire-spinning mechanism, and the wire rod is spread on a roller and transported along the roller. A suitable wire-spinning temperature is selected to keep the wire rod in a high-temperature austenitized state, avoid the precipitation of network carbides in the wire-spinning stage, and provide favorable conditions for the subsequent rapid nucleation of bainite and sorbite. Specifically, the wire-spinning temperature is controlled to be 930°C.
[0048] The online molten salt rapid quenching process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first salt bath tank for the front stage molten salt treatment, so that the wire rod is cooled at a cooling rate of 42°C / s, and quickly skips the network carbide interval from the high-temperature austenite state to enter the bainite and pearlite mixed phase area, inhibiting the formation of network carbides. The high-temperature austenite phase transforms into a structure mainly composed of a small amount of quenched bainite and a large amount of fine lamellar interlayer sorbite. It is then conveyed by a roller through the second salt bath tank for the rear stage molten salt treatment. The process of the molten salt treatment in the front stage is to increase the molten salt temperature, reduce the molten salt circulation volume, promote the isothermal tempering of the formed quenched bainite and troostite structures, take into account rapid processing and avoid excessive softening, so as to regulate the strength-plasticity matching of the wire rod. Specifically, the molten salt temperature of the front stage molten salt treatment is 400°C, the processing time is 30s, the molten salt circulation volume is 660t / h, and the molten salt temperature rise is ≤10°C; the molten salt temperature of the rear stage molten salt treatment is 450°C, the processing time is 200s, the molten salt circulation volume is 410t / h, and the molten salt temperature rise is ≤3°C.
[0049] The roller slow cooling process controls the opening of the insulation cover to blow hot air ≥ 250°C above the two salt bath tanks of the online molten salt rapid quenching treatment to the conveyor roller, and the conveyor roller conveys the wire rod through the insulation cover to promote further toughening of the wire rod structure and improve the tempering and softening effect of the wire rod. Specifically: the wire rod is controlled to be cooled to 278°C at a slow cooling rate of 0.2°C / s; the coiling process is used to coil the wire rod into a coil by a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage.
[0050] Comparative Example 7: A method for manufacturing a hot-rolled wire rod, which differs from Example 4 in that: the manufacturing method is manufactured according to a process flow of rolling → spinning → online molten salt rapid quenching → air cooling, and the air cooling process adopts opening the insulation cover to control the wire rod to be cooled to 270°C at a slow cooling rate of 1.3°C / s, and the hot-rolled wire rod finished product is obtained after it comes off the line.
[0051] The hot rolled wire rods obtained in Examples 1 to 4 and Comparative Examples 1 to 7 were subjected to microstructure and performance tests, and the comparative results are shown in Table 1 below: Table 1. Comparison of microstructure and properties of different hot-rolled wire rod compositions and manufacturing methods
[0052] In the above table, the lamellar spacing of comparative example 2 refers to the lamellar spacing of pearlite, and the others refer to the lamellar spacing of tempered bainite. It can be seen from the comparison results of Example 1 and Comparative Example 1 that, compared with reducing the carbon content and eliminating alloying elements, a higher level of network carbides will still be produced under air cooling conditions, which will have an adverse effect on the plasticity and toughness of the matrix and the fluctuation of mechanical properties. At the same time, the strengthening effect will be weakened due to the weak cooling rate. Under the strong air cooling effect after spinning, the radial difference of strong plasticity and the fluctuation of mechanical properties will be further increased. The present invention adopts the design of carbon containing B chemical composition combined with the online molten salt rapid quenching technology to form a quenching method. The structure is mainly composed of a mixed phase of fire bainite and fine lamellar spacing troostite structure, and then appropriately heated and isothermally tempered to effectively improve abnormal structures such as network carbide, martensite, coarse pearlite, etc.; it can be seen from the results of Examples 1 to 4 that the present invention can simplify the component system, reduce material costs, and achieve complex phase structure regulation, while taking into account the strong and plastic performance matching and rapid production of the wire rod. The wire rod can achieve a tensile strength of 1330~1380MPa and a cross-sectional shrinkage rate of 35%~40%, and then be used in fields such as 1960MPa grade steel strands, which is beneficial to reduce the risk of wire breakage during the wire drawing and torsion process of the stranded steel.
[0053] From the comparison results of Example 1 and Comparative Example 2, it can be seen that the wire rod adopts a higher spinning temperature, which makes the structure in a high-temperature austenite state, can inhibit the segregation of components and avoid the formation of network carbides due to too low temperature, providing favorable conditions for promoting bainite quenching and lamellar refinement, while reducing the restriction on rolling temperature.
[0054] From the comparison results of Example 2 and Comparative Example 3, it can be seen that the lower the molten salt temperature and the longer the treatment time of the front-stage molten salt treatment, the more coordinated with the hardenability of B, the more beneficial it is to inhibit the network carbides and lamellar coarsening, increase the supercooling of austenite, the shear driving force of the needle-shaped quenched bainite transformation is dominant, and the nucleation rate is accelerated, which is beneficial to promoting the refinement of the sorbite structure lamellar, and can improve the matrix strength. However, if the molten salt temperature is too low and the treatment time is too long, the quenched bainite transformation increases and the internal stress of the organization increases, which will increase the difficulty of subsequent tempering softening, affect the plasticity and production efficiency of the wire rod, and increase production energy consumption.
[0055] From the comparison results of Example 2 and Comparative Example 4, it can be seen that the higher the molten salt temperature and the shorter the treatment time of the front-stage molten salt treatment, the stronger the diffusion driving force of the sorbite transformation, the easier it is to form the sorbite lamellar structure and the lower the difficulty of improving the plasticity of tempering. However, if the molten salt temperature is too high and the treatment time is too short, it is not conducive to the formation of quenched bainite, and there is a risk of coarsening the sorbite lamellar layer, thereby losing the matrix strength.
[0056] From the comparison results of Example 3 and Comparative Example 5, it can be seen that the higher the molten salt temperature and the longer the treatment time of the later molten salt treatment, the carbon atom diffusion rate can be increased, which provides more driving force for the isothermal tempering and toughening of the quenched bainite and troostite structures, can reduce the stress and dislocation density in the quenched bainite, improve the plasticity and toughness of the structure, and the uniformity of the tempering of the surface and core structures. However, if the molten salt temperature is too high and the treatment time is too long, the atomic diffusion rate will be accelerated, and the cementite of the quenched bainite and troostite will gradually coarsen and aggregate, which will cause excessive softening and significantly lose the matrix strength, while also leading to an increase in production cycle and energy consumption.
[0057] From the comparison results of Example 3 and Comparative Example 6, it can be seen that the lower the molten salt temperature and the shorter the treatment time of the later molten salt treatment, the slower the diffusion rate of carbon atoms, which is beneficial to reducing the risk of carbide coarsening and excessive strength loss, reducing production energy consumption, and improving production efficiency. However, if the molten salt temperature is too low and the treatment time is too short, it is difficult to provide more thermal power for tempering, which will affect the stress release and tempering effect, increase the brittleness of the wire rod, and the difference between the surface and core structures. When subjected to stress, the core is prone to fracture due to stress concentration.
[0058] From the comparison results of Example 4 and Comparative Example 7, it can be seen that the temperature of the wire rod after leaving the molten salt is relatively high. The use of roller slow cooling can avoid insufficient plasticity of the wire rod due to insufficient slow cooling. At the same time, slow cooling promotes further toughening of the wire rod structure and improves the tempering and softening effect of the wire rod.
[0059] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. Any equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for manufacturing high-strength multi-phase hot-rolled wire rod for 1960 MPa grade stranded wire, characterized in that: The manufacturing method includes: The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.79% to 0.83%, Si: 0.20% to 0.40%, Mn: 0.67% to 0.78%, B: 0.001% to 0.008%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; the wire rod is spun into wire rod at a spinning temperature of ≥890°C, and then subjected to online molten salt In the rapid quenching treatment, the wire rod first undergoes the front-end molten salt treatment, so that the wire rod is cooled at a cooling rate of ≥36℃ / s, and enters the mixed phase region of bainite and pearlite from the austenite state, forming a structure mainly composed of quenched bainite and sorbite. The wire rod then undergoes the rear-end molten salt treatment to increase the molten salt temperature, promote the isothermal tempering of the quenched bainite and sorbite structures, and finally passes through the roller to slowly cool, and is made into a hot-rolled wire rod with a microstructure consisting of tempered sorbite, tempered bainite and ferrite.
2. The method for manufacturing a high-strength multi-phase hot-rolled wire rod for 1960 MPa grade stranded wire according to claim 1, characterized in that: Before the rolling, the soaking temperature of the heating furnace is controlled to be 1180-1220° C., and the soaking time in the furnace is 150-220 min.
3. The method for manufacturing a high-strength multi-phase hot-rolled wire rod for 1960 MPa grade stranded wire according to claim 1, characterized in that: During the rolling, the initial rolling temperature is controlled to be 1080-1100° C., the final rolling temperature is controlled to be 900-940° C., and the final rolling reduction is controlled to be 25%-30%.
4. The method for manufacturing a high-strength multi-phase hot-rolled wire rod for 1960 MPa grade stranded wire according to claim 1, characterized in that: During the spinning process, the spinning temperature is controlled to be 890-930°C.
5. The method for manufacturing high-strength multi-phase hot-rolled wire rod for 1960 MPa grade stranded wire according to claim 1, characterized in that: The molten salt temperature of the front-stage molten salt treatment is 400-450° C., and the treatment time is 30-200 seconds; the molten salt temperature of the back-stage molten salt treatment is 450-480° C., and the treatment time is 50-200 seconds.
6. The method for manufacturing high-strength multi-phase hot-rolled wire rod for 1960 MPa grade stranded wire according to claim 5, characterized in that: The molten salt circulation rate of the front-stage molten salt treatment is 460~660t / h, and the molten salt temperature rise is ≤10°C; the molten salt circulation rate of the back-stage molten salt treatment is 320~410t / h, and the molten salt temperature rise is ≤3°C.
7. The method for manufacturing high-strength multi-phase hot-rolled wire rod for 1960 MPa grade stranded wire according to claim 5, characterized in that: The roller slow cooling controls the wire rod to be cooled to below 280° C. at a slow cooling rate of ≤0.6° C. / s for coiling.
8. A high-strength multi-phase hot-rolled wire rod for 1960 MPa grade stranded wire, characterized in that: The hot-rolled wire rod is manufactured by the method for manufacturing high-strength multi-phase hot-rolled wire rod for 1960 MPa grade stranded wire according to any one of claims 1 to 7.
9. The high-strength multi-phase hot-rolled wire rod for 1960 MPa grade stranded wire according to claim 8, characterized in that: The volume percentage of the tempered bainite is 68% to 78%, the interlamellar spacing is 70 to 115 nm, the volume percentage of the tempered bainite is 20% to 30%, the network carbide grade of the hot-rolled wire rod is grade 0, and the mechanical property same-circle difference is ≤38 MPa.
10. The high-strength multi-phase hot-rolled wire rod for 1960 MPa grade stranded wire according to claim 8, characterized in that: The hot-rolled wire rod has a diameter of 8.0-15.0 mm, a tensile strength of 1330-1380 MPa, and a cross-sectional shrinkage rate of 35%-40%.
Citation Information
Patent Citations
Prestressed steel strand, wire rod for prestressed steel strand and their production methods
CN112301287B
Direct quenching bath for high-speed wire after spinning and quenching method of direct quenching bath
CN115478150A
Heat treatment method of high-carbon steel wire rod
CN116287592A
Wire rod for hot-rolled complex-phase 1860MPa-grade stranded wire and manufacturing method of wire rod
CN119020571A
High-strength complex-phase hot-rolled wire rod for 1960 MPa bridge cable and manufacturing method of high-strength complex-phase hot-rolled wire rod
CN119162428A
Cited By
High-strength complex-phase hot-rolled wire rod for 2260MPa-grade stranded wire and manufacturing method of high-strength complex-phase hot-rolled wire rod
CN121046732A
High-strength complex-phase hot-rolled wire rod for 2200MPa-grade stranded wire and manufacturing method of high-strength complex-phase hot-rolled wire rod
CN121046736A
High-strength complex-phase hot-rolled wire rod for 2230 MPa grade stranded wire and manufacturing method of high-strength complex-phase hot-rolled wire rod
CN121065587A
A high-strength multiphase hot-rolled wire rod for 2230MPa grade stranded wire and its manufacturing method
CN121065587B
High-strength complex-phase hot-rolled wire rod for 2160MPa-grade stranded wire and manufacturing method of high-strength complex-phase hot-rolled wire rod
CN121065588A